Improving Helpdesk Capability in Perum Peruri Through Service Catalog Management Based on ITIL V3 - M. Attaqwa Ananta Budi; M. Gilvy Langgawan Putra; Lovinta Happy Atrinawati (International Institute for Advanced Science & Technology (IIAST), 2022)
Perusahaan Umum Percetakan Uang Republik Indonesia (PERUM PERURI) is a government entity responsible for the printing and security of coins and bank notes of Bank Indonesia (BI) which is required to implement Good Corporate Governance (GCG). Previous evaluation of information technology governance indicates that PERUM PERURI needs to improve its helpdesk capability in providing IT services to all users. The first thing that needs to be done is developing and maintaining IT service catalogue, which serves as sole source of information regarding all of IT services provided by the IT division. The design of Service Catalog Management uses framework ITIL Version 3 best practice in services. This research uses Design Thinking Approach as a method in implementing a solution that has 5 stages, namely: Empathy, Define, Ideate, Prototype and Test. The implementation of the Design Thinking aims to produce an idea execution that meets user needs through understanding the user's character and providing a helicopter view (Prototype) of the Business Service Catalog so that users can provide experiences and feedback so that they can be a solution to the problems faced by the Business Service Catalog. This research produces two documents from Service Catalog Management, namely: 1). Business Service Catalog;, and 2). Technical Service Catalog. It is hoped that this Service Catalog document will be able to become a complete source of information, knowledge, reference regarding services to service users and service providers in order to minimize problems regarding helpdesk Peruri IT Division.